Teaching Evolutionary Biology at Lower and Upper Secondary Schools - Hlaváčová, Lucie (Scientia in educatione, 2015)
The research aims to verify main biological topics associated with teaching of theory of evolution and natural selection and the most frequently applied teaching methods for the interpretation of these evolutionary topics. The total of 213 teachers from lower secondary schools and 137 teachers from upper secondary schools - from all regions of the Czech Republic – took part in the research. The data were gathered via an online questionnaire. The data from lower secondary teachers and upper secondary teachers were elaborated separately. The results show that Human Evolution and the Origin of life are the most common topics taught at lower and upper secondary schools in the context of evolutionary biology. Some evolutionary topics are dealt with more deeply at upper secondary schools. The most frequently applied teaching methods for evolutionary topics are exposition, discussion and watching movies (documentaries). Some of the identified teaching methods are more frequently applied at lower secondary schools than upper secondary schools.